Shortages Without Frontiers: Antimicrobial Drug and Vaccine Shortages Impact Far Beyond the Individual! - Beraud, Guillaume (Frontiers in Medicine, 2021)
Among increasingly common drug shortages, antimicrobial drug and vaccine shortages are the most frequently reported. This could be related to the smaller size of the market, compared to statins or antidepressant drugs. But there are multiple causes to shortages, such as flawed manufacturing processes, modification of quality control processes and scarcity of raw materials. Besides, concentration of manufacturing in emerging economies, dependence on a single producer and pressure on profit margins amplify the consequences of any manufacturing problem. Antimicrobial drug shortages have an impact on patient outcomes and antimicrobial resistance (AMR) by leading to choices of alternatives with an inadequately large spectrum, and consequently with deleterious side effects and increased costs. Moreover, vaccine shortages result in controversies exacerbated by the antivax community. Given the transmissibility of infectious diseases, antimicrobial drug and vaccine shortages will impact both individual and population health through herd effect. For these reasons, they represent a worldwide threat that goes beyond impact at the individual level. There has been no coordinated response to this threat hitherto. In order to provide an adequate response plan, precise data on shortage occurrences and their causes are a prerequisite. Moreover, efficient action will not be possible without a transnational will. An example of useful action could be: -Incorporating a standardized survey into the WHO surveillance programs on antimicrobial use. -Creating a communication channel between pharmaceutical companies, providers and national agencies to recognize upcoming shortages. -Licensing some laboratories so as to manufacture out-of-stock drugs, for the duration of the shortage.